THE ASSOCIATION OF DYSLIPIDEMIA WITH INTRAPERITONEAL INFLAMMATION AND PERITONEAL DIALYSIS TECHNIQUE SURVIVAL - Stepanova, N.; Burdeyna, O.; Dudar, I.; Driyanska, V.; Snisar, L.; Shifris, I.; Krasyuk, E.; Shimova, A. (Ukrainian Journal of Nephrology and Dialysis, 2017)
The aim of the study was to determine the relationship between the dyslipidemia, intraperitoneal inflammation and peritoneal dialysis (PD) survival. Patients and methods. A total of 40patients with end-stage renal disease treated with continuous ambulatory peritoneal dialysis (PD) have been included in a prospective, observational study (average age was 49.3 ± 12.7). All patients were determined the blood lipid spectrum and IL-10, TNF-a, MCP-1 levels in peritoneal dialysis effluent (PDE). PD adequacy indicators evaluated by determining the concentration of urea and creatinine in plasma, urine and dialysate, calculated weekly creatinine clearance (CrCl), dialysis (Kt/ Vd), renal (Kt/ Vr) and total weekly urea clearance (Kt/ V). Results. Dyslipidemia defined as increase of atherogenic lipoprotein fractions and inhibition ofHDL cholesterol was identified in 70% of the PD-patients. LDL cholesterol level and, accordingly, an atherogenic index (AI) were significantly dependent on the duration of PD treatment (R2 = 2.18 ± 0.15 (95% CI 1.87, 2.5), p < 0,0001 and R2 = 2.77 ± 0.27(95% CI 2.2, 3.3), p < 0,0001). The blood levels of total cholesterol, LDL-C and TG in the patients with diabetes were significantly higher compared with the diabetes-free patients (p = 0.007, p = 0.001 andp = 0.02, respectively). Reducing the HDL cholesterol level was associated with high intraperitoneal production of pro-inflammatory mediators TNF-a (r = - 0.53;p = 0.001) and anti-inflammatory IL-10 (r = - 0.783;p <0.0001), whereas hypertriglyceridemia and high VLDL cholesterol are associated with an increase of MCP-1 (r = 0.6;p = 0.0003 and r = 0.55;p = 0.002, respectively). The Cox proportional hazards regression analysis demonstrated the significant effect of VLDL cholesterol, LDL cholesterol and AI on the survival of PD technique survival (x2 = 24.8; p < 0.0001). The results of the Kaplan–Meier analysis and log-rank test also identified that there was a significant difference in the cumulative technical survival rate between the patients with AI level < 3.5 and > 3.5 (log-rank test: x2 = 19.8, P = 0.001. Conclusions. Our results can be considered dyslipidemia in PD-patients not only as a traditional risk factor for CVD, but also as a predictor of chronic intraperitoneal inflammation and decrease of PD technical survival.